7x+3+2x=3(13-x)

Simple and best practice solution for 7x+3+2x=3(13-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x+3+2x=3(13-x) equation:


Simplifying
7x + 3 + 2x = 3(13 + -1x)

Reorder the terms:
3 + 7x + 2x = 3(13 + -1x)

Combine like terms: 7x + 2x = 9x
3 + 9x = 3(13 + -1x)
3 + 9x = (13 * 3 + -1x * 3)
3 + 9x = (39 + -3x)

Solving
3 + 9x = 39 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
3 + 9x + 3x = 39 + -3x + 3x

Combine like terms: 9x + 3x = 12x
3 + 12x = 39 + -3x + 3x

Combine like terms: -3x + 3x = 0
3 + 12x = 39 + 0
3 + 12x = 39

Add '-3' to each side of the equation.
3 + -3 + 12x = 39 + -3

Combine like terms: 3 + -3 = 0
0 + 12x = 39 + -3
12x = 39 + -3

Combine like terms: 39 + -3 = 36
12x = 36

Divide each side by '12'.
x = 3

Simplifying
x = 3

See similar equations:

| y=-7+9 | | x^3+12x^2+16x=0 | | N+6=14+5n | | -8(3x+2)=2x-3x | | 6x+22= | | A(x)=x(14-x) | | -x+sqrt(2)-2=0 | | -14+3a=-8+4a | | 14+4x+2y=142 | | 2(3.5p+7)=7(p+1) | | 6x+5=10x+40 | | 6x+5=10x+20 | | 15/42.625-2=7/22.625+13/4 | | 4.39=-1.6c+7.59 | | 4x+6+2y+8=142 | | -7n-2=16 | | y^2-6y-5x=-14 | | -0.21=log(x) | | 20+130+p=180 | | 4t+17=7+5f | | 25x^3-10x= | | x^4+4x^2+1=0 | | X=y^2-6 | | -8(2-x)=416 | | 3x+2=96 | | (x-2)squared=50 | | (x^3+x^2+x+1)(13x-9)= | | 6k-16=2k+4 | | (x^4-x^2-2x+6)=0 | | (8-6i)-4=x-(1+yi) | | -3(2p+14)-28=2(p+15)+12 | | 6x-3=4(x+22) |

Equations solver categories